2000
DOI: 10.1111/j.1365-2672.2000.tb05333.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli in foods

Abstract: SUMMARY Studies describing the survival of Escherichia coli in foods, more often than not use the O157:H7 serovar as the target organism. Whilst E. coli O157:H7 is undoubtedly the predominant agent of concern for foodborne disease caused by enterohaemorrhagic E. coli (EHEC), a consequence of this concern is the commonly held view that this one serovar is ‘atypical’ in its response to stress conditions and therefore better able to survive adverse environments. Many of the studies published do not make compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…The consensus seems to be that E. coli O157:H7 is well suited to adverse conditions even though little direct evidence supports the hypothesis that this pathogen is substantially different from other E. coli serotypes in AR abilities (30). Most AR studies are based on only a few non-O157 STEC strains of the same serotype, which reduces the statistical power to detect significant differences between groups.…”
Section: Discussionmentioning
confidence: 98%
“…The consensus seems to be that E. coli O157:H7 is well suited to adverse conditions even though little direct evidence supports the hypothesis that this pathogen is substantially different from other E. coli serotypes in AR abilities (30). Most AR studies are based on only a few non-O157 STEC strains of the same serotype, which reduces the statistical power to detect significant differences between groups.…”
Section: Discussionmentioning
confidence: 98%
“…Non-pathogenic E. coli was used as a possible model for E. coli O157:H7. There have been no reports of significant differences in survival and growth characteristics between E. coli O157:H7 and nonpathogenic E. coli (McClure & Hall, 2000;Yokoigawa, Takikawa, & Kawai, 1999) in minimally processed vegetables (MPV). However, more evidence is needed to show that the strain used is an appropriate model i.e.…”
Section: Introductionmentioning
confidence: 98%
“…In the human stomach, STEC O157 must survive the low pH of gastric fluid. In order to understand the ecology of STEC O157 and establish effective control measures against the bacterium, extensive research has been done on bacterial stress responses (5,24). Although some of these studies have shown the importance of cross-protection in stress resistance (5,20,33), the association between more than three types of stress has seldom been investigated.…”
mentioning
confidence: 99%